2023
DOI: 10.1021/acs.inorgchem.3c00163
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isostructural Intermetallic Sn–Pb–Bi–Pt Platform Materials for Catalytic Investigations

Abstract: The isostructural region (Sn,Pb,Bi)Pt has been established over a wide range of the quasi-ternary section of the quaternary phase diagram. A synthesis protocol was developed, and single-phase compounds were thoroughly characterized, revealing linear relationships between the volume of the unit cell and the substitution degree for the NiAs type of crystal structure. Together with the already established (Pb,Bi)Pt series, the isostructural cut at 50 atom % Pt forms an ideal platform to independently investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(73 reference statements)
0
1
0
1
Order By: Relevance
“…Post-transition metal cations, including Pb 2+ , Sn 2+ , Bi 3+ , and Sb 3+ , have a wide variety of applications in electrochemical energy storage [1,2] high-temperature superconductivity [3][4][5], catalysis [5][6][7], gas sensors [8][9][10], birefringent material [11][12][13][14], nonlinear optical crystals [15][16][17][18], etc. By analyzing many existing studies, it was found that the introduction of post-transition metal cations containing stereochemically active lone-pair electrons is a good strategy to enhance optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transition metal cations, including Pb 2+ , Sn 2+ , Bi 3+ , and Sb 3+ , have a wide variety of applications in electrochemical energy storage [1,2] high-temperature superconductivity [3][4][5], catalysis [5][6][7], gas sensors [8][9][10], birefringent material [11][12][13][14], nonlinear optical crystals [15][16][17][18], etc. By analyzing many existing studies, it was found that the introduction of post-transition metal cations containing stereochemically active lone-pair electrons is a good strategy to enhance optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Das System eignet sich bei Pt-Gehalt, den Einfluss der atomaren und der elektronischen Struktur bei der Elektrokatalyse zu untersuchen. 55) Hartenbach, Schleid und Claudia Wickleder haben Y…”
unclassified